2013
DOI: 10.1111/tpj.12225
|View full text |Cite
|
Sign up to set email alerts
|

A subcellular tug of war involving three MYB‐like proteins underlies a molecular antagonism in Antirrhinum flower asymmetry

Abstract: These two authors contributed equally to this work. SUMMARYThe establishment of meristematic domains with different transcriptional activity is essential for many developmental processes. The asymmetry of the Antirrhinum majus flower is established by transcription factors with an asymmetric pattern of activity. To understand how this asymmetrical pattern is established, we studied the molecular mechanism through which the dorsal MYB protein RADIALIS (RAD) restricts the activity of the MYB transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 35 publications
2
120
0
Order By: Relevance
“…interacting with SvDIV1B as in other species (Raimundo et al, 2013). However, to confirm this hypothesis, the function of SvRAD needs to be further investigated.…”
Section: Ray3 and Svdiv1b Play Antagonistic Roles During Ray Petal Dementioning
confidence: 99%
See 2 more Smart Citations
“…interacting with SvDIV1B as in other species (Raimundo et al, 2013). However, to confirm this hypothesis, the function of SvRAD needs to be further investigated.…”
Section: Ray3 and Svdiv1b Play Antagonistic Roles During Ray Petal Dementioning
confidence: 99%
“…Floral bilateral symmetry in A. majus involves the action of CYC and DICH that activate RAD, which in turn down-regulates DIV activity in dorsal petals (Raimundo et al, 2013;Corley et al, 2005;Costa et al, 2005;Almeida et al, 1997). However, there has been no evidence as to whether DIV can feedback to regulate these genes during flower development.…”
Section: Regulatory Relationships Of Floral Symmetry Genes Are Alterementioning
confidence: 99%
See 1 more Smart Citation
“…The symmetry of a flower influences how easily a pollinator can acquire the reward by specifying the presence and position of landing platforms and occluded palates that require force to open. In Antirrhinum majus a transcriptional network comprising TCP and MYB family transcription factors has been shown to specify zygomorphy (bilateral symmetry) [69][70][71][72]. The mutants generated during these studies have provided insight into how pollinators forage to optimise their energy return.…”
Section: E Optimising Efficiency Of Reward Acquisitionmentioning
confidence: 99%
“…Although DIV is an important player in ventral petal identity (Galego and Almeida, 2002;Rose et al, 1999), it is expressed in both ventral and dorsal petals (Almeida et al, 1997;Galego and Almeida, 2002). Recently, it has been shown that RAD negatively regulates DIV function via protein-protein interaction (Raimundo et al, 2013). DIV must form a heterodimer with another MYB protein, DIV-and-RAD-interacting-factor (DRIF), to function as a transcription factor in establishment of ventral petal identity.…”
Section: Structure and Expression Analyses Of Floral Symmetry Associamentioning
confidence: 99%